Case Report: Successful Chimeric Antigen Receptor T Cell Therapy in Haploidentical-Allogeneic Stem Cell Transplant Patients With Post-Transplant Lymphoproliferative Disorder - Yan, Nan; Wang, Na; Zhang, Peiling; Wang, Gaoxiang; Mao, Xia; Peng, Dan; Kuang, Dong; Chen, Liting; Zhu, Li; Zhou, Jianfeng; Zhang, Yicheng; Cao, Yang (Frontiers in Oncology, 2021)
Background: Epstein–Barr virus-associated post-transplant lymphoproliferative disorder (EBV-PTLD) is potentially fatal complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Rituximab has been proven to dramatically improve the prognosis of patients with EBV reactivation and PTLD. However, reports on curative management of refractory PTLD are scarce Case presentation: in the study, we described successful management of two patients with EBV-PTLD with chimeric antigen receptor T-cell (CAR-T) therapy. Conclusion: The present results demonstrated that patients with EBV-PTLD may benefit from CAR-T therapy and the toxicity is manageable. Further studies are needed to verify these findings.